Nhận thức lại những quan điểm của chủ nghĩa Mác-Lênin về văn hoá - Phạm, Duy Đức (2011)
Tác giả: Phạm Duy Đức, PGS,TS; Nguyễn Duy Bắc, PGS,TS; Trần Văn Bính, GS,TS; Bùi Kim Chi, ThS; và những người khác -- Từ khóa: Chủ nghĩa Mác-Lênin; Văn hoá